2000
DOI: 10.1136/sti.76.5.398
|View full text |Cite
|
Sign up to set email alerts
|

Short course oral prednisolone therapy in chronic abacterial prostatitis and prostatodynia: case reports of three responders and one non-responder

Abstract: Objective: To report on a small group of patients with chronic abacterial prostatitis/chronic pelvic pain syndrome treated with oral corticosteroids in order to suggest a hypothesis for a future randomised controlled trial. Design: A retrospective, observational report. Results: Three out of the four patients reported improvement in symptoms following steroid treatment. Conclusions: These reports suggest that there is scope for conducting a randomised, placebo controlled study to investigate the role of oral c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 9 publications
(6 reference statements)
0
8
1
Order By: Relevance
“…A pilot study of patients with unclassified CP/CPPS treated with oral corticosteroids found that three of four patients responded favorably [29]. Randomized, controlled trials need to verify these findings.…”
Section: Immunogeneticsmentioning
confidence: 79%
“…A pilot study of patients with unclassified CP/CPPS treated with oral corticosteroids found that three of four patients responded favorably [29]. Randomized, controlled trials need to verify these findings.…”
Section: Immunogeneticsmentioning
confidence: 79%
“…A randomized, placebo-controlled study of rofecoxib in CPPS showed symptomatic improvement after 1 month with high-dose therapy, but changes in the CPSI did not reach statistical significance, primarily because of an unusually large placebo effect [34]. Limited case reports suggest that some patients may benefit from therapy with steroids [35] or full immunosuppression [36], though the side effects may be unacceptably high if the patient does not require these drugs for another concomitant problem. A randomized, placebo-controlled trial of pentosan polysulfate (Elmiron; Alza Pharmaceuticals, Mountain View, CA) in CPPS showed a slightly greater improvement in symptoms over placebo after 16 weeks, but the difference was not statistically significant [37].…”
Section: Anti-inflammatory Therapymentioning
confidence: 93%
“…A recent RCT involving combination prednisone and levofloxacin treatment for 2 or 4 weeks showed statistically significant improvement in the treatment group compared to controls in several outcomes, including NIH-CPSI and quality of life scores 25. In another study, three of four patients with CP/CPPS treated with corticosteroids showed improvement of symptoms 26. No rigorous large-scale clinical trials have demonstrated statistically significant symptomatic improvement in CP/CPPS patients, suggesting these drugs might be useful in less severe cases or in combination with other drugs.…”
Section: Overview Of Existing Datamentioning
confidence: 98%